Variability of Arctic sea‐ice topography and its impact on the atmospheric surface drag. Issue 10 (15th October 2014) - Castellani, G.; Lüpkes, C.; Hendricks, S.; Gerdes, R.
Abstract Over the polar oceans, near‐surface atmospheric transport of momentum is strongly influenced by sea‐ice surface topography. The latter is analyzed on the basis of laser altimeter data obtained during airborne campaigns between 1995 and 2011 over more than 10, 000 km of flight distance in different regions of the Arctic Ocean. Spectra of height and spacing between topographic features averaged over 10 km flight sections show that typical values are 0.45 m for the mean height and about 20 m for the mean spacing. Nevertheless, the variability is high and the spatial variability is stronger than the temporal one. The total topography spectrum is divided into a range with small obstacles (between 0.2 m and 0.8 m height) and large obstacles (≥0.8 m). Results show that large pressure ridges represent the dominant topographic feature only along the coast of Greenland. In the Central Arctic, the concentration of large ridges decreased over the years, accompanied by an increase of small obstacles concentration and this might be related to decreasing multiyear ice. The application of a topography‐dependent parameterization of neutral atmospheric drag coefficients reflects the large variability in the sea‐ice topography and reveals characteristic differences between the regions. Based on the analysis of the two spectral ranges, we find that the consideration of only large pressure ridges is not enough to characterize the roughness degree of an ice field, and the values of drag coefficients are in most regions strongly influenced by small obstacles.